Curriculum designers information system for institution of higher learning in Malaysia - Jusoh, Yusmadi Yah; Abdullah, Rusli; Alwi, Nor Hayati; Thong, Chee Ling (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Nowadays, the institutions of higher learning (IHL) are competing and moving forward on providing the best quality of curriculum to their stakeholders such as the industries and students. However, designing a curriculum is considered time consuming, tedious and error prone if are not well managed. Whereas with the support of information system (IS), it is able to increase efficiency of curriculum designers in terms of reducing time, error and effort during the curriculum design process. The literature concludes that there are numerous curriculum design information systems in the market and they are used to facilitate the work of curriculum design. However, it is found that they are lack of step-by-step guidance during the curriculum design process. Moreover, the research on IS model for curriculum design that provides guidance in accomplishing the task is scarce. Guidance is important to curriculum designers, in the absence of guidance the curriculum designers do what is best and that is often not good enough. The proposed model and a system developed to guide and assist curriculum designers during the curriculum design process.